PENERAPAN TEKNOLOGI SILASE DAN AMONIASI SEBAGAI SOLUSI KETAHANAN PAKAN - Riesi Sriagtula; Qurrata Aini; Hilda Susanty; Ridho Kurniawan Rusli; Aronal Arief Putra (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service (PKM) activity aimed to increase the knowledge and skills of breeders in processing and preserving agricultural waste as a solution for feed security. The specific objective to be achieved was to increase livestock production through the provision of feed according to livestock needs, both in terms of quality and quantity. This PKM activity was carried out at the Harapan Sejahtera Farmer Group located in Aia Pacah Village, Koto Tangah District, Padang City. Counseling and practice provided to breeders were in the form of processing Sweet Corn Straw Silage (Zea mays saccharata Sturt) and Rice Straw (Oryza sativa) into Ammoniation. The method used in empowering the target group was learning techniques in the form of providing theory, counseling and practice to members of the target group. The result of this activity showed that the Harapan Sejahtera Farmers Group can provide motivation to farmers to process agricultural waste into quality feed. After counseling, farmers become aware and motivated in processing agricultural waste into quality feed for feed security, especially in the dry season. In addition, managing agricultural waste, and turned it into beneficial products with economic value.